Marketing Adult Education for Megaprojects in the Northwest Territories - Andrew P. Hodgkins (Journal of Contemporary Issues in Education, 2008)
This empirical research inquiry examines the influence that the current economic climate - driven by the extraction of non-renewable resources currently underway in the Northwest Territories - is having on adult education policy and program development. A qualitative methodology involving open-ended interviews was chosen for this study to better understand how local realities of labour market influenced educational policy and its implications for policy process and practice. The inquiry gathers perceptions of those given authority and responsibility for developing policy on behalf of northerners, and also those affected by such policies. Interviews were conducted during the summer of 2005 and included policy planners at Aurora College and other stakeholders involved in northern development, adult education and training. Findings suggest that the cooptation of adult education by market forces has occurred despite increased local autonomy through recent Aboriginal self-governance initiatives. Implications for community sustainability and governance are examined within this context.